How did sanctions impact Myanmar? - Ajmani, Manmeet Singh; Joshi, Pramod Kumar; Kishore, Avinash; Roy, Devesh (2018)
With continued international concern over the treatment of Rohingyas in Myanmar, some commentators have suggested the use of sanctions to varying degrees. This would not be the first time that Myanmar faced sanctions. The United States imposed sanctions on Myanmar in 2003 and revoked them only in 2016, and Washington has recently also begun imposing some targeted sanctions following the Rohingya crisis. In this article, we discuss the impacts and coping strategies related to the sanctions imposed on Myanmar, which lasted over a decade.